Gastrointestinal cancer prevention policies in Iran: A policy analysis of agenda-setting using Kingdon's multiple streams. (March 2021) - Kabiri, Neda; Khodayari-zarnaq, Rahim; Khoshbaten, Manouchehr; Arab-Zozani, Morteza; Janati, Ali
Highlights: High cost of cancer diagnosis is a main problem in Iran due to international sanctions. Limited access to cancer medicine is another problem in Iran. Actors need political support to push the issue of cancer prevention on the agenda. Presence of the policy entrepreneurs can press for policy change. Inter-sectoral collaboration should be strengthen to success in policy implementation. Abstract: Background: Gastrointestinal cancers continue to claim the lives of thousands of individuals. Fortunately, primary prevention, which focuses on interventions to change unhealthy lifestyle behaviors, can lessen the negative effects and decrease the economic burden of these cancers. The purpose of this paper is to assess the likelihood of adopting gastrointestinal cancer prevention policies through the lens of Kingdon's theory of agenda setting. Methods: A qualitative study was conducted using document review and face-to-face interviews with 22 key informants from different stages of the policymaking process of gastrointestinal cancer prevention program in Iran. We used purposive sampling. Our analysis of documents and interview were guided based on Kingdon's multiple streams (problem stream, policy stream, and political stream). Results: Based on the results of this study the important factors of problem stream are as below. The high cost of gastrointestinal cancer diagnostic services dramatically affect patient's financial affordability to essential cancer-related services. Consequently, most of the cancers show distant metastasis at the time of diagnosis, imposing catastrophic expenses to patients, society, and the health systems. In the policy stream, participants mentioned the importance of the cancer registry system in the country that provides a clear source of information for decision-makers to plan for early diagnostic services. Under the political stream, the national and international supports provide a favorable climate for this issue. Conclusion: Now that a window of opportunity for gastrointestinal cancer prevention policymaking is created, there is a need for greater efforts to strengthen the inter-sectoral collaboration. The presence of the policy entrepreneurs during this period can press for policy change, however, actors need political support from the highest level of the governance to push this issue on the agenda. Policy summary: This paper is seeking to have impact on the policies related to prevention of gastrointestinal cancers in Iran.